Constructing Democracy: The Role of LGBTQ+ Rights in Israeli Identity Formation - Avarino,Thomas (2024)
In recent years, the focus that LGBTQ+ rights have been receiving internationally has led to the reconsideration of their status, in both national and international contexts. Among many examples, this shift has been significant in Israel, where political discourse has made LGBTQ+ rights more and more visible. This study aims to present the processes of how Israeli politicians have incorporated LGBTQ+ rights into their political discourse in order to strengthen the national identity and to portray a progressive image of the country both nationally and abroad. The research found recurrent patterns in the ways in which social groups and issues are framed by Israel's political landscape. They were identified through the use of thematic analysis of political speeches, combined with an analysis of scholarly literature. By unfolding the complexities of the discourse, which presents homonationalist and orientalist features, the research intends to provide insights about Israel's stances regarding human rights, and about how the country intends to portray itself as an example of democracy in the MENA region.
Keywords: LGBTQ+; national identity; speeches; homonationalism